SIKAP KONSUMEN DAN POLA PEMBELIAN SUSU GREENFIELDS DI KOTA BANDAR LAMPUNG - Ghina Putri Fadhilah; Adia Nugraha; Rabiatul Adawiyah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
This study aims to analyze the attitude of consumers toward the purchase of Greenfields milk in Bandar Lampung City in order to investigate the purchasing pattern of Greenfields milk by consumers towards Greenfields milk. This re search was conducted at Chandra Superstore Tanjung Karang, Chamart Wayhalim, Lion Superindo Lampung, Gelael Lampung, Transmart Lampung, MM Surya Pagar Alam, and Indomaret Plus Ryacudu Korpri 2.  The overlay of this research method was a survey with an accidental technique. Thus, the respondents in this study were 56 Greenfield milk consumers who had bought/consumed Greenfield’s milk at least once during their last month. Research data were analyzed using Fishbein Multi-attribute analysis and descriptive analysis. Data collection was conducted from April to Mei 2021. The results showed that the Greenfields milk consumers of Greenfields milk with the most possible attribute, namely the taste attribute. The highest amount of Greenfields milk purchased was UHT milk with full cream flavor. The average number of purchases of Greenfields milk per customer was 3.369ml per month and the average frequency of purchasing Greenfields milk is two times a month.   Keywords: customer attitudes, buying patterns, and Greenfields milk.